Analisis Kejadian Stunting pada balita di wilayah kerja Puskesmas Tebing Tinggi Kabupaten Empat Lawang tahun 2024 - Pebriani, Tri Josih; Gustina, Erma; Zaman, Chairil; Suryanti, Dewi (Avicenna: Jurnal Ilmiah, 2025)
Background: Stunting in toddlers can result in impaired growth and development of children due to chronic malnutrition and recurrent infections, which is characterized by their body length or height being below standard. The prevalence of stunting in Empat Lawang Regency is higher (18,5%) than Suoth Sumatra Province (14%). Based on nutritional reporting data, the highest number of stunting cases occuraed in Tebing Tinggi District. Method: The research method used is quantitative with an analytical survey research design with a cross-sectional approach. The population in this study were parents of toddlers in the Tebing Tinggi Community Health Center working area with a sample size of 100 respondents and the sampling technique was purposive sampling. Univariate and bivariate data analysis using the square test. Results: Based on the results of univariate analysis, it was found that age 12-23 months (50,5%), male gender (50,5%), exclusive breastfeeding (73,7%), income not according to minimum wage (66,3%), LBW (3,2%), and stunting (36,8%). The result of statistical tests using chi square showed that there was a relationship between age (P Value = 0,40), exclusive breastfeeding (P Value = 0,002), BBLR (P Value = 0.047) and the incidence of stunting in toddlers. Kesimpulan: There is a relationship between age, gender, exclusive breastfeeding, income and LBW with the incidence of stunting. It is hoped that health workers in the Puskesmas work area will provide education to the public about stunting and the factors that influence it. Keywords: Exclusive Breastfeeding, LBW, Stunting